(untitled) (ModaPalavra e-periódico, 2015)
This article analyzes the costumes for carnival in the front lines in plots developed by Rosa Magalhães for the Imperatriz Leopoldinense, in the years 2001 to 2005. Seek correspondences between the sketches and the justifications prepared by the carnival.